Expression of the beta subunit of spectrin in nonerythroid cells. - Nelson, W J (1983)
Antibodies raised against electrophoretically purified chicken erythrocyte beta subunit of spectrin, called "beta-spectrin," have been used to demonstrate the presence of an immunoreactive form of this polypeptide in nonerythroid tissues. Immunoautoradiography shows that, in chicken erythrocytes, this antiserum reacts with beta-spectrin (Mr 220,000) and another polypeptide (Mr 230,000) that, by two-dimensional tryptic peptide analysis, shows extensive homology with beta-spectrin but not with the alpha subunit of spectrin, called "alpha-spectrin." Immunoautoradiography and immunoprecipitation of various chicken tissues with this antiserum shows that either one variant or both variants of beta-spectrin are expressed. Indirect immunofluorescence reveals that the antiserum reacts with a plasma membrane-associated component of erythroid and some nonerythroid cells. Particularly strong fluorescence is observed in skeletal and cardiac muscle cells where beta-spectrin appears to form a grid-like network along the inner surface of the sarcolemma. The noncoordinated distribution of alpha- and beta-spectrin variants indicates that their expression may be tailored to the functional requirements of the plasma membrane in different cells.